Diskresi Hakim dalam Penjatuhan Hukuman Bagi Pelaku Penganiayaan yang Menyebabkan Luka Berat: Analisis Putusan Nomor 221/Pid.B/2024/PN Rhl - Ferdiansyah, Ferdiansyah; Kusno, Kusno; Siregar, Ahmad Ansyari (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to analyze judicial discretion in sentencing perpetrators of aggravated assault resulting in serious bodily injury. The research method employed is normative legal research with a statute approach and a case study approach, which is analyzed qualitatively through content analysis. The results show that the defendant was charged alternatively with a primary indictment of attempted murder, a subsidiary indictment of aggravated assault resulting in serious bodily injury, and a lesser subsidiary indictment of simple assault. The charges by the Public Prosecutor were in line with the subsidiary indictment of aggravated assault resulting in serious bodily injury as supported by the Visum et Repertum. Conversely, the judge’s verdict, based on the lesser subsidiary indictment of simple assault, emphasizes judicial discretion. Judicial discretion is an effort to balance the enforcement of positive law and the achievement of substantive justice by considering the values that live in society (living law). The decision reflects the struggle between formal legality and contextual substantive justice. Therefore, more precise guidelines are needed regarding the limits and parameters of judicial discretion, especially in cases that intersect with living law. Improving the quality of the Visum et Repertum and strengthening judges’ capacity to understand living law are also important to strive for in order to achieve a responsive and just judicial system.